Eixos de sustentabilidade do programa/plano cidades sustentáveis de cascavel: análise da conformidade com a norma abnt iso 37120/2017 - Teske, Kamyla Taysa (2024)
The growth of cities and the search for a balance between economic growth, quality of life and environmental preservation have made sustainability a priority in urban environments. To guide public policies in this direction, various metrics and indicator systems have been developed. However, many of these only focus on specific parts of sustainability, or are difficult to interpret. Thus, this study focuses on evaluating the pillars of sustainability present in the Sustainable Cities Plan (PCS) in Cascavel, with the aim of aligning these aspects with the criteria established by ISO Standard 37120/2017. To achieve this objective, an applied and qualitative study was carried out, using specific tools to assess the possible certification of the city according to ISO 37120/2017 standards. The method involves a case study approach, focussing on the assessment of municipal sustainability and includes stages such as bibliographical and documentary research, tabulation of ISO 37120/2017 indicators, as well as empirical validation using semi-structured interviews with experts. The data was analysed using Iramuteq software. The results indicate that Cascavel has strengths such as a diversified economy, high school enrolment rates, and effective water management. However, critical areas such as air quality, sewage treatment, and the promotion of urban green areas need urgent improvement. The research highlights the importance of participatory governance and strategic partnerships for sustainable development. The implementation of ISO 37120/2017, with a continuous monitoring system and staff training, is essential to ensure sustainable and transparent urban development. This study provides a detailed analysis of urban sustainability indicators in Cascavel, suggesting specific actions for certification and promotion of a sustainable and resilient city model.